CEOs as corporate ambassadors: deciphering leadership communication via Twitter - Wu, T; Reynolds, J; Wu, J; Schlegelmilch, BB (Emerald Publishing Limited, 2021)
Purpose This study aims to analyze the ways in which chief executive officers (CEOs) communicate via Twitter and help develop guidelines for effective tweeting strategies that can leverage Twitter in leadership communication.